Reading Like A Replicant: Blade Runner 2049, Pale Fire, and the Archival Embodiment of Literature - Campbell, Lee (Imaginations)

(untitled) (York University, 2023)
If androids dream of electric sheep, do replicants read analog novels? In the dystopian sci-fi world of Blade Runner 2049 (2017), literature plays a complex role. In particular, the film engages in a multi-leveled way with Vladimir Nabokov's novel Pale Fire (1962). A hardcover copy of the book appears in one scene, and it is quoted and covertly referenced in others. These appearances are like metafictive keys to a pattern of possible meanings, through which the film both embodies and reflects upon its method of archival replication. Translating between codex, screen, and holographic media, the film reanimates its source materials, dramatises the affinity between literary texts and embodied life, and suggests that literature may be a vector of resistance to techno-capitalist archival control.